Health Care Utilization and Costs of Patients With Prostate Cancer in China Based on National Health Insurance Database From 2015 to 2017 - Bai, Lin; Wushouer, Haishaerjiang; Huang, Cong; Luo, Zhenhuan; Guan, Xiaodong; Shi, Luwen (Frontiers in Pharmacology, 2020)
Background: Prostate cancer is one of the highest increasing cancers in medical costs with tremendous economic burden, but the evidence on health care utilization and medical expenditure of prostate cancer was absent in China. Objective: This study aimed to analyze health care utilization and direct medical costs of patients with prostate cancer in China. Methods: Health care service data with a national representative sample of basic medical insurance beneficiaries between 2015 and 2017 were obtained from the China Health Insurance Association database. We conducted descriptive and statistical analyses of health care utilization, annual direct medical costs and composition based on cancer-related medical records. Health care utilization was measured by the number of hospital visits and the length of stay. Results: A total of 3,936 patients with prostate cancer and 24,686 cancer-related visits between 2015 and 2017 were identified in the database. The number of annual outpatient and inpatient visits per patient differed significantly from 2015 to 2017. There was no obvious change in length of stay and annual direct medical costs from 2015 to 2017. The number of annual visits per patient (outpatient: 3.0 vs. 4.0, P<0.01; inpatient: 1.5 vs. 2.0, P<0.001) and the annual medical direct costs per patient (US$2,300.1 vs. US$3,543.3, P<0.001) of patients covered by the Urban Rural Resident Basic Medical Insurance (URRBMI) were both lower than those of patients covered by the Urban Employee Basic Medical Insurance (UEBMI), and the median out-of-pocket expense of URRBMI was higher than that of UEBMI (US$926.6 vs. US$594.0, P<0.001). The annual direct medical costs of patients with prostate cancer in Western regions were significantly lower than those of patients in Eastern and Central regions (East: US$4011.9; Central: US$3458.6; West: US$2115.5) (P<0.001). Conclusions: There was an imbalanced distribution of health care utilization among regions in China. The direct medical costs of Chinese patients with prostate cancer remained stable, but the gap in health care utilization and medical costs between two different insurance schemes and among regions still needed to be further addressed.